Practices and barriers to screening for hyperglycaemia in pregnancy among providers of antenatal care in Jos, Nigeria - Lucius C. Imoh; Abdulazis S. Longwap; Favour E. Haruna; Oghale J. Asieba; Joy P. Istifanus; Joy A. Imoh; Mathilda E. Banwat (AOSIS, 2022)
Background: Screening for hyperglycaemia in pregnancy (HIP) is an important component of comprehensive antenatal care. Screening practices for HIP in Nigeria and factors that influence these practices are not well understood. Objective: We examined the screening practices for HIP and their correlates among antenatal healthcare providers (AHPs). Methods: This descriptive cross-sectional study of AHPs providing all levels of antenatal care was conducted between August 2019 and September 2019 in Jos, Nigeria. Eligible AHPs completed a semi-structured, self-administered questionnaire, and data were analysed for adherence to recommended screening practices such as World Health Organization, International Association of Diabetes and Pregnancy Study Groups and National Institute for Health and Care Excellence guidelines. Results: Of the 128 respondents included in the analysis, 59 (46.1%) were male and 69 (53.9%) were female. The mean participant age was 35.7 years (standard deviation: ± 8.5 years). Most (68.0%) screened all pregnant women (universal screening) for gestational diabetes mellitus. Fasting blood glucose (77.0%) and random blood glucose (55.7%) were the most common tests used. Only 27 respondents (22.1%) screened using the 75 g oral glucose tolerance test, and most were doctors, AHPs in faith-based or government institutions, tertiary institutions and facilities with availability of automated glucose analysers (p  0.05 for all). Conclusion: Screening practices for HIP among the AHPs do not generally conform to best practices. Hence, there is an urgent need for implementation of universal guidelines and provision of regular updates and basic glucose measuring devices for AHPs at all healthcare levels.